Long‐term effectiveness of a hyaluronic acid soft tissue filler in patients with facial lipoatrophy, morphological asymmetry, or debilitating scars. (22nd June 2020) - Grablowitz, Doris; Ivezic‐Schoenfeld, Zrinka; Federspiel, Ira G.; Gehl, Benjamin; Kopera, Daisy; Prinz, Martin
Abstract: Background: Soft tissue fillers are typically used for rejuvenating an aging face; they are also employed in the treatment of certain pathologic conditions, including facial lipoatrophy, morphological asymmetry, and debilitating scars. Aims: The aim of this clinical study was to evaluate the effectiveness and safety of Princess® Volume (PV) in patients with facial lipoatrophy (FLA), morphological asymmetry (MA), or debilitating scars (DS). Patients/Methods: This prospective, noncomparative, multicenter clinical study consisted of five visits spread across 36 weeks. Up to 60 adult patients suffering from moderate facial lipoatrophy, facial morphological asymmetry, or debilitating scars on the face were to be included. All patients were treated with an HA filler (PV). Results: At Week 4, the treatment success rate in the SP was 98% (95% CI [90.4%, 100%]), as assessed by both the investigators and the patients. According to the independent reviewer, the success rate was 93% (95% CI [82.7%, 98.0%]). At Week 24, the effect was maintained in most patients, with success rates of 80% as evaluated by the investigator and 79% by the patient (95% CI [67.6%, 89.8%] and [65.6%, 88.4%], respectively). At Week 36, success rates dropped to 61% as assessed by the investigator and 59% by the patient (95% CI [46.8%, 73.5%] and [45.0%, 71.9%], respectively). Conclusions: The clinical study has proven that Princess ® Volume is a safe and effective therapeutic solution for the correction of soft tissue defects in FLA and facial MA, but limited success rate to DS.